2000
DOI: 10.1007/s004679900278
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of heavy proteinuria and progression risk factors in children undergoing urinary screening

Abstract: To evaluate the prevalence and incidence density of heavy proteinuria and chronic renal insufficiency (CRI) and the factors related to disease progression, 10,288,620 urinary screenings of elementary and junior high-school students from 1992 to 1996 were studied retrospectively. Urinary screening included pH, protein, occult blood, and glucose measurements. Blood sample analysis included total protein, albumin, A/G ratio, blood urea nitrogen, creatinine (Cr), antistreptolysin O titer, C3, cholesterol, hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 12 publications
2
38
1
Order By: Relevance
“…Bakr et al found that gender, age, or socioeconomic status had no effect on the prevalence of urinary abnormalities (11). In contrast, Lin et al showed that microscopic urinary abnormalities were more common in males than females (26). Urine specific gravity was more than 1.020 in the present study that may indicate a relative dehydration.…”
Section: Discussioncontrasting
confidence: 92%
“…Bakr et al found that gender, age, or socioeconomic status had no effect on the prevalence of urinary abnormalities (11). In contrast, Lin et al showed that microscopic urinary abnormalities were more common in males than females (26). Urine specific gravity was more than 1.020 in the present study that may indicate a relative dehydration.…”
Section: Discussioncontrasting
confidence: 92%
“…This is in part the result of the historical absence of a common definition of CKD and a well-defined classification of its severity. Mass screening programs to detect CKD in children have been well established in several Asian countries, such as Kuwait, Japan, Taiwan and Korea [13][14][15][16]. Conversely, screening programs have not been adopted in Europe, but urine screening dipsticks have routinely been used in healthy children for decades in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and aggressive management are essential to improve outcomes in young patients with CKD (8,9) .…”
Section: Introductionmentioning
confidence: 99%